PEMANFAATAN LMS DI ERA PANDEMI PADA STUDI KASUS SMAN 1 BANJARAN - Hefi Harpiyah Rachman; Muhamad Prakarsa Al Qadr Saleh (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
Changes in the provision in learning activities in schools in the current pandemic conditions cause schools in Indonesia to apply learn from home one of them in SMAN 1 Banjaran which was originally the learning process carried out in schools to be online. This causes the school to use technology in learning. This research aims to explain the use of learning management system (LMS) as one of the media used in e-learning learning in the era of the Covid-19 pandemic. The method used in this research is literature studies because data is drawn from various relevant references such as in books and research journals. Learning management system is used as a platform in e-learning created. The programming language used is PHP using HTML, CSS with MySQL as a database. Development methods are used using Unifield Modeling Language (UML). The results of research conducted in the creation of e-learning by utilizing this learning management system can provide ease of online learning in the current Covid-19 pandemic era. The results of the study found that teachers and students can do learning through this LMS-based e-learning well.